Improving the properties of an Al matrix composite fabricated by laser powder bed fusion using graphene–TiO2 nanohybrid - Ghazanlou, Siavash Imanian; Ghazanlou, Siamak Imanian; Ghazanlou, Sroush Imanian; Hosseinpour, Saman; Liao, Yiliang; Javidani, Mousa (Journal of Alloys and Compounds, 2023)
The impact of graphene–TiO2 nanohybrid reinforcement on an aluminum matrix after the laser powder bed fusion process was investigated. The microstructure characteristics, mechanical properties, wear resistance, and corrosion behavior of the fabricated nanocomposite structures with different contents of the graphene–TiO2 nanohybrid were compared with those of the pure aluminum and aluminum matrix composite reinforced with separated graphene and nano-TiO2. X-ray diffraction, Raman and X-ray photoelectron spectroscopy, mechanical and tribological characterization, fractography, and corrosion assessments were performed to identify the role of the graphene–TiO2 nanohybrid in improving the properties of the Al matrix composite after reinforced laser powder bed fusion. In the presence of graphene–TiO2 nanohybrid in the Al matrix, Al4C3 formation could not be detected, which may be due to the existence of TiO2 nanoparticles on the surface of the graphene. Despite this result, the Al4C3 structure was identified in LPBF Al matrix composite containing separated graphene and nano-TiO2. The results indicated a synergistic effect between the graphene and TiO2 particles in the nanohybrid structure. In the unified nanohybrid structure, due to the raising surface roughness of graphene with the presence of TiO2 on its surface, strong interfacial bonding between the graphene–TiO2 nanohybrid and Al matrix is created. Thus, the graphene–TiO2 nanohybrid incorporated within the Al matrix can bridge between the subsurface cracks and reduces the cracks propagation in the matrix, thereby enhancing the mechanical properties, wear resistance, and corrosion behavior of the composite.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Aluminum; Composite; Graphene–TiO; LPBF; Property enhancement